2020
DOI: 10.1080/0309877x.2020.1795093
|View full text |Cite
|
Sign up to set email alerts
|

Academic faculty conceptualisation and understanding of plagiarism – a Thai university exploratory study

Abstract: Her research interests focus on university students' and academic staff's perceptions of plagiarism and the development of plagiarism frameworks in higher education.Caroline Walker-Gleaves, Professor of Education at Newcastle University, is a lecturer and educator who works at the intersections of pedagogic theory and practice, teachers and their values and beliefs, the design of learning environments incorporating pedagogic principles, and SEND studies. Academic faculty conceptualisation and understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…We have explained that there have been cases where accused plagiarists did not receive any formal punishment. This can be because the university did not take serious attention in handling the plagiarism issue (Khathayut and Walker-Gleaves 2021 ). In regard to Djaali’s five doctoral students (Rosser 2022 ; Sumandoyo 2017 ), they were even given a chance to rewrite the doctoral thesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have explained that there have been cases where accused plagiarists did not receive any formal punishment. This can be because the university did not take serious attention in handling the plagiarism issue (Khathayut and Walker-Gleaves 2021 ). In regard to Djaali’s five doctoral students (Rosser 2022 ; Sumandoyo 2017 ), they were even given a chance to rewrite the doctoral thesis.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Khathayut and Walker-Gleaves ( 2021 ) about the understanding of plagiarism at a university in Thailand found that many lecturers have limited understanding and low awareness of plagiarism. This will affect how the university sees plagiarism, whether it is considered a serious problem, and how it takes action to handle it.…”
Section: Discourse Culture and Powermentioning
confidence: 99%
“…They do citations and use correct references because plagiarism in academic work is a crime. Khathayut and Walker-Gleaves (2021) have mentioned that higher education staff can avoid plagiarism by keeping writing honestly through paraphrasing. Based on Table 7, eight items are asked to the English lecturers about creating information.…”
Section: %mentioning
confidence: 99%
“…On the other hand, the lecturers had both limited understanding and low awareness of plagiarism, and their conceptualization as a problem of scholarship and moral behavior was unsophisticated at best and a matter of ambivalence at worst [20].…”
Section: Introductionmentioning
confidence: 99%